The effects of persistent organic pollutant dioxin on reverse cholesterol transport pathway of hdl in differentiated 3t3-l1 adipocytes - Ali, Roslina; Abdul Rahman, Thuhairah Hasrah; Abd Muid, Suhaila; Salim, Norita; Ramzi, Ahmad; Hamimah, Siti; Razali, Ruzi Hamimi; Chainchel Singh, Mansharan Kaur (Research and Innovation Division, Universiti Teknologi MARA (UiTM) Selangor, 2025)
Cardiovascular disease (CVD) the leading cause of mortality globally occurs primarily due to coronary artery disease caused by hypertension, diabetes and dyslipidemia. In addition to the above-mentioned risk factors, persistent organic pollutants (POPs) which include dioxin also play a role in CVD. They are transported by lipoproteins and accumulate in adipose tissue with low-density lipoprotein (LDL) found to be the main transporter of lipid-soluble POPs. However, very-LDL (VLDL) and high-density lipoprotein (HDL) have also been associated with lipid-soluble POPs in humans. An in-vitro study looking at the effects of dioxin in reverse cholesterol transport (RCT) of high-density lipoprotein cholesterol (HDL-c), an anti-atherogenesis pathway was undertaken to further understand it’s mechanism of action. MATERIALS AND METHOD: 3T3-L1 preadipocytes were differentiated into mature adipocytes according to manufacturer instructions. A cholesterol efflux capacity assay was performed using mature adipocytes loaded with fluorescence-labelled cholesterol and treated with dioxin concentrations of 1,10,30 nm and dioxin 30 nm together with rosiglitazone (0.005 μmol/ml). The movement of labelled cholesterol from the cells to the acceptor (HDL) was quantified with the intensity of fluorescence-labelled cholesterol measured at 485 nm excitation and 523 nm emission. RESULTS AND DISCUSSION: The percentage of cholesterol efflux using dioxin concentrations of 1 and 10 nm and HDL was lower than that of HDL alone. However, the highest Dioxin concentration (30 nm) showed comparable results with HDL after a 4 hours efflux incubation period. Dioxin together with rosiglitazone and HDL showed unexpected results with a lower percentage of cholesterol efflux. This shows that Dioxin and rosiglitazone did not significantly increase the ability of HDL to promote cholesterol efflux in mature adipocytes as it should function.